2023
DOI: 10.3390/su152115309
|View full text |Cite
|
Sign up to set email alerts
|

Can Grassroots Governments’ Environmental Attention Effectively Improve Air Pollution? Empirical Evidence from Satellite Remote Sensing Technology

Kai Lin,
Yanli Shi,
Hong Xu

Abstract: Air pollution poses a global challenge, prompting governments worldwide to implement environmental policies aimed at its mitigation. However, grassroots management is key to the effectiveness of pollution management. Traditional air monitoring, ranging from a specific point to broader areas, has inherent limitations. In contrast, satellite remote sensing technology offers extensive spatial and temporal coverage, enabling real-time monitoring of data transmission. Can the amalgamation of grassroots governance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…On the other hand, environmental target constraints can reflect the intrinsic drive of local governments in environmental governance. They are willing to disclose environmental goals and accept public supervision [40]. Therefore, regions with such constraints invariably exhibit a higher level of environmental consciousness.…”
Section: Empirical Analysis 41 Baseline Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, environmental target constraints can reflect the intrinsic drive of local governments in environmental governance. They are willing to disclose environmental goals and accept public supervision [40]. Therefore, regions with such constraints invariably exhibit a higher level of environmental consciousness.…”
Section: Empirical Analysis 41 Baseline Resultsmentioning
confidence: 99%
“…Ref. [40] examined the influence of local governments' environmental concerns on local atmospheric pollution by measuring eco-nomic growth constraints and environmental target constraints. They found that in regions without economic pressure, local governments can effectively achieve environmental target constraints, leading to a significant reduction in atmospheric pollution.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation